Motor Vehicle Tax Amnesty Between Fiscal Inclusivity And The Risk of Declining Tax Discipline - M. Aziz Fatur Rachman; Daniel Pamungkas; Nickson Nikolas Situmorang; Ratna Septiyanti; Mega Metalia (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze public perceptions of the vehicle tax amnesty program from two main perspectives: fiscal inclusivity and the risk of declining tax discipline. The research method employed is descriptive quantitative, with data collected through an online questionnaire (Google Form) completed by 102 respondents from various age groups, professions, and levels of vehicle ownership. The results indicate that the public’s level of awareness regarding the tax amnesty program is very high (95.1%). Most respondents (82.4%) believe that the program helps alleviate the financial burden on society, and 70.6% agree that the amnesty can improve taxpayer compliance. However, 50% of respondents also consider that the program poses a risk of decreasing taxpayer discipline in the future, as it may encourage delays in tax payments until similar programs are offered again. These findings highlight a dilemma between achieving fiscal inclusivity and maintaining long-term tax compliance. Therefore, local governments need to balance tax incentive policies with taxpayer education strategies to achieve fiscal objectives without undermining tax discipline.